Blunt and penetrating cervical trauma. Issue 9 (September 2021) - Awad, Zaid; Jacques, Thomas
Abstract: Trauma to the cervical region may result in critical injury to the airway, the neck vasculature, and the pharynx or oesophagus. These three systems should be systematically assessed, alongside ATLS protocols, in all patients presenting with blunt or penetrating trauma to the head and neck region. The majority of trauma centres now have a policy of selective neck exploration based on clinical and radiological findings. It is therefore essential to be aware of the symptoms and clinical signs of injury of key neck structures, so that neck exploration can be performed promptly in patients who require it.